2021
DOI: 10.3390/app11020634
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Evaluation of Computational Fluid Dynamics Approach for Inhalation Exposure Assessment: Case Study for Biocide Spray

Abstract: Consumer products contain chemical substances that threaten human health. The zero-dimensional modeling methods and experimental methods have been used to estimate the inhalation exposure concentration of consumer products. The model and measurement methods have a spatial property problem and time/cost-consuming problem, respectively. For solving the problems due to the conventional methodology, this study investigated the feasibility of applying computational fluid dynamics (CFD) for the evaluation of inhalat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In contrast, Koch et al [6] observed that ConsExpo tended to overpredict the experimental air concentrations in their setup. Additionally Delmaar and Meesters [26], as well as Park and Lee [83] observed largest deviations between ConsExpo's model prediction and measurement in the early stages of exposure, whereas Park et al [82] found that the evaluated tools all tended to deviate from the measurements in the later stages of the exposure experiment. The uncertainty of both input parameters and measurements could be one of the reasons for the observed inter-study differences.…”
Section: Information On External Evaluation Of the Models-inhalation ...mentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, Koch et al [6] observed that ConsExpo tended to overpredict the experimental air concentrations in their setup. Additionally Delmaar and Meesters [26], as well as Park and Lee [83] observed largest deviations between ConsExpo's model prediction and measurement in the early stages of exposure, whereas Park et al [82] found that the evaluated tools all tended to deviate from the measurements in the later stages of the exposure experiment. The uncertainty of both input parameters and measurements could be one of the reasons for the observed inter-study differences.…”
Section: Information On External Evaluation Of the Models-inhalation ...mentioning
confidence: 97%
“…Recently Park and Lee [83] undertook an evaluation of the ConsExpo spray model, contrasting model simulations with both experimental concentrations after biocide spray application and with computational fluid dynamics (CFD) simulations. The experiment followed particle concentrations during 60 min in the air of a 30 m 3 climate chamber.…”
Section: Information On External Evaluation Of the Models-inhalation ...mentioning
confidence: 99%